PENANAMAN NILAI-NILAI RELIGIUS PADA PESERTA DIDIK MELALUI KEGIATAN KEAGAMAAN DI SMP IT AN NURIYAH SEKAYU - Suci Hidayati; Muhammad Win Afgani; Fajri Ismail (ADIBA : JOURNAL OF EDUCATION, 2023)
Religious value is one of the character values that is used as an obedient attitude and behavior in carrying out the teachings of the religion adhered to. These religious values are needed by students in facing the changing times and moral degradation as it is today. This study aims to analyze the effectiveness of instilling religious values in religious activities at SMP IT An Nuriyah Sekayu. Primary data research uses qualitative methods by way of observation and interviews during religious activities. The data obtained were then analyzed by carrying out the process of identification, categorization, and then reduced to be displayed descriptively and finally conclusions/verification were carried out. The results showed that the inculcation of religious values in the religious activities of SMP IT An Nuriyah Sekayu was carried out by providing religious knowledge at the morning assembly or during class lessons, setting a good example, and then cultivating religious values was carried out by habituating these activities. religion every day. This study also found factors that support and hinder the inculcation of religious values in religious activities at SMP IT An Nuriyah Sekayu. Factors that support the inculcation of religious values in these religious activities are permission from the parents of students to their sons and daughters to carry out religious activities at school and factors that hinder the inculcation of religious values in religious activities are the difficulty of changing old habits of students plus a lack of good grades. -religious values in students. From this study it can be concluded that it is very important to instill religious values in students through religious activities. The impact of instilling religious values through religious activities on social behavior can be seen from several indicators that have been achieved from the purpose of holding these activities, such as children getting used to participating in religious activities held, carrying out prayers on time, children behaving in good manners to people who are more parents or peers and used to be disciplined in all matters.